A Biofunctional Hydrogel/Nanofiber Bilayer Scaffold Delivering EGF and TGFβ3 for Advanced Nasal Tissue Reconstruction - Yilmaz, Hilal; Gursoy, Sevda; Torkay, Gulsah; Saraj, Shhd; Karzoun, Louna; Kose, Alpay; Insel, Mert Akin; Yildirim, Ridvan; Ozturk, Ayca Bal; Koyuncu, Ayse Ceren Calikoglu; Gunduz, Oguzhan; Ustundag, Cem Bulent (WILEY-V C H VERLAG GMBH, 2025)
Nasal reconstruction usually requires a two-stage reconstructive approach using natural or synthetic grafts and skin flaps. There are many disadvantages to using grafts and flaps, and the need for a tissue engineering (TE) product to overcome these disadvantages is obvious. Cartilage grafts and skin flaps can be designed in nasal reconstruction using a bilayer scaffold prepared with TE. In this study, we show that the designed biomimetic gelatin methacryloyl-ciprofloxacin/polycaprolactone-collagen (GelMA-CIP/PCL-COL) bilayer scaffold can be biofunctionalized using the electrospray method. The hydrogel layer was coated with epidermal growth factor (EGF)-loaded polyvinyl alcohol (PVA) nanoparticles, while the nanofiber layer was coated with transforming growth factor (TGF beta 3)-PVA nanoparticles. We report the GelMA-CIP@PVA-EGF/PCL-COL@PVA-TGF beta 3 bilayer scaffold with nanoparticles of 304 +/- 14.5 nm diameter, growth factor delivery for 28 days, 2.115 +/- 0.367 tensile strength, which is very close to nasal cartilage (NC), and suitable swelling and degradation properties for cartilage and skin treatment. We also verify the biocompatibility of the produced scaffolds with human mesenchymal stem cells using the MTT test. As a result, the bilayer scaffold may have the potential for future use in nasal TE. It is envisaged that it could provide dynamic guidance for very complex nasal reconstruction procedures.
Keywords: EGF; electrospraying; gelatin methacryloyl; nasal tissue engineering; PCL; TGF beta 3; MESENCHYMAL STEM-CELLS; GELATIN METHACRYLOYL GELMA; IN-VITRO; CHONDROGENIC DIFFERENTIATION; CARTILAGE; RELEASE; DRUG; COLLAGEN; SURGERY; REGENERATION; Materials Science; Polymer Science